ANALISIS EKONOMI USAHA SAPI POTONG DI LAHAN PERKEBUNAN SAWIT DAN KARET - S. Rusdiana; R. Hutasoit; J. Sirait (Universitas Sebelas Maret, 2016)
The study was conducted in the village of Pulo Bandring Tanah Rakyat District of Asahan in North Sumatra Province. The study was conducted in 2015 using the method of field survey on 30 respondent beef cattle farmers in a way purposive random sampling. The primary data obtained through interviews directly in the field with farmers beef cattle, which refers to the questionnaire has been prepared, while secondary data obtained from the Extension Service, Plantation, Agriculture and Livestock local, then the data collected was processed and tabulated descriptive, quantitative and economic analysis. The purpose of this paper is to determine the economic analysis in the beef cattle business in a manner shepherd breeder dilahan palm and rubber plantations in Asahan. The results showed that the net income of the business of cattle by means of grazing dilahan oil palm and rubber plantations around Rp.3.185.000/breeder/year with B/C ratio of 1.2. Labor breeder beef cattle by about 20,000 working time/day 8 hours is calculated based on the first working Hok / day. For the breeders of beef cattle in the Village People's District of Pulobandring Asahan immediately in the push towards commercial business, so that the cattle were reared by farmers to grow, can produce well, and pertamabahan body weight increases, so that the sale value of cattle higher in terms of the market price of cattle.